2022
DOI: 10.3390/w14192980
|View full text |Cite
|
Sign up to set email alerts
|

Flood Uncertainty Estimation Using Deep Ensembles

Abstract: We propose a probabilistic deep learning approach for the prediction of maximum water depth hazard maps at high spatial resolutions, which assigns well-calibrated uncertainty estimates to every predicted water depth. Efficient, accurate, and trustworthy methods for urban flood management have become increasingly important due to higher rainfall intensity caused by climate change, the expansion of cities, and changes in land use. While physically based flood models can provide reliable forecasts for water depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Notably, current flood risk assessments under climate change uncertainties remain underexplored and tend to be limited to individual factors. As an illustration, Chaudhary (2022) introduced a probability-centric deep learning technique to ascertain uncertainties from intensified rainfall due to variables like climate change and urban expansion [200]. It is also crucial to acknowledge that extreme events, such as typhoons, can catalyze secondary hazards like landslides.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Notably, current flood risk assessments under climate change uncertainties remain underexplored and tend to be limited to individual factors. As an illustration, Chaudhary (2022) introduced a probability-centric deep learning technique to ascertain uncertainties from intensified rainfall due to variables like climate change and urban expansion [200]. It is also crucial to acknowledge that extreme events, such as typhoons, can catalyze secondary hazards like landslides.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Techniques such as ensembling and distillation are known to improve model calibration (Hansen and Salamon, 1990;Lakshminarayanan et al, 2017) and reduce model churn (Hidey et al, 2022). However, these techniques may not always be practical due to the computational cost -ensembling requires K trained models for inference.…”
Section: Related Workmentioning
confidence: 99%
“…They indicated that the selection of hydrological models (e.g., model structure) is a critical source of uncertainty based on fuzzy and analysis of variance methods. Chaudhary et al, (2022) developed a deep learning ensemble model that is trained with hydrodynamic model outputs to predict urban flood hazards at high spatial resolution. They estimated total predictive uncertainty in terms of aleatory and epistemic uncertainty by focusing on model inputs and model parameters (e.g., deep learning model's weights).…”
Section: Introductionmentioning
confidence: 99%